Product name detection from user forums - Peh, Wei Leng (2014)
People nowadays are strongly influenced to using acronym and not full names when referring to Smartphone or other products on forums. This leads to an increasing number of different naming convention (e.g., full names, acronym names or certain names referring to more than one product) used when referring to a certain product. Therefore, this report presents the proposed techniques to automatically identify the product names from online forums.